2021
DOI: 10.1101/2021.06.01.446676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Infects Syncytiotrophoblast and Activates Inflammatory Responses in the Placenta

Abstract: SARS-CoV-2 infection during pregnancy leads to an increased risk of adverse pregnancy outcomes. Although the placenta itself can be a target of virus infection, most neonates are virus free and are born healthy or recover quickly. Here, we investigated the impact of SARS-CoV-2 infection on the placenta from a cohort of women who were infected late during pregnancy and had tested positive for SARS-CoV-2 by qRT-PCR at delivery. SARS-CoV-2 genomic and subgenomic RNA was detected in 23 out of 55 placentas (41%). T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 55 publications
3
21
0
4
Order By: Relevance
“…We reviewed the literature and identified 56 previously published and well-documented cases of diffuse SARS-CoV-2 placentitis 6,7,14–26. A summary of the pregnancy-related features of these, together with our 4 new cases, is provided in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…We reviewed the literature and identified 56 previously published and well-documented cases of diffuse SARS-CoV-2 placentitis 6,7,14–26. A summary of the pregnancy-related features of these, together with our 4 new cases, is provided in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Immune activation at the maternal-fetal interface and in fetal cord blood has been observed in prenatal SARS-CoV-2 infection Although the immune and inflammatory response to SARS-CoV-2 in pregnancy is only beginning to be characterized, early data show a proinflammatory cytokine phenotype in pregnant women with active SARS-CoV-2, with interferon-gamma (IFN-γ), IL-1β, and IL-6 most implicated, particularly in cases of severe COVID-19 disease [77,78]. Several studies have demonstrated the potential for maternal SARS-CoV-2 infection to stimulate an intense placental immune and inflammatory response [79][80][81], both in the presence (rare) [81] and absence (more common) [80,82,83] of direct SARS-CoV-2 infection of the placenta. Substantial infiltration of maternal immune cells into the placenta has been observed in cases of severe maternal COVID-19 disease, adverse neonatal outcomes, and heavy placental SARS-CoV-2 viral burden [81].…”
Section: Mia and Placental Immune Activation In Response To Sars-cov-...mentioning
confidence: 99%
“…Several studies have demonstrated the potential for maternal SARS-CoV-2 infection to stimulate an intense placental immune and inflammatory response [79][80][81], both in the presence (rare) [81] and absence (more common) [80,82,83] of direct SARS-CoV-2 infection of the placenta. Substantial infiltration of maternal immune cells into the placenta has been observed in cases of severe maternal COVID-19 disease, adverse neonatal outcomes, and heavy placental SARS-CoV-2 viral burden [81]. In addition, maternal SARS-CoV-2 infection is associated with hyperplasia and/or increased density of fetal placental macrophages or Hofbauer cells, typically in the absence of Hofbauer cell infection [80,84].…”
Section: Mia and Placental Immune Activation In Response To Sars-cov-...mentioning
confidence: 99%
“…ACE2 is also expressed within placental tissues [52], and is involved in regulating fetal myocardial growth and lung and brain development [53]. A recent pre-print study showed that blocking ACE2 with an anti-ACE2 antibody reduced placental SARS-CoV-2 infection [54]. This is one of a number of studies that have demonstrated that the placenta is susceptible to SARS-CoV-2 [53,55], and may also be responsive to spike proteins, which have been identified at low concentrations in plasma from recipients of the Moderna vaccine [56].…”
Section: Bioactivity Of the Sars-cov-2 Spike Proteinmentioning
confidence: 99%